#### Answer

See the picture below.

#### Work Step by Step

The parent function is $g(x)=(\frac{1}{3})^x$ (with red) the given function is $f(x)=(\frac{1}{3})^x-2$ (with blue).
The parent function can be graphed by calculating a few coordinates and connecting them with a smooth curve:
$g(-2)=\frac{1}{3}^{-2}=9$
$g(-1)=\frac{1}{3}^{-1}=3$
$g(0)=\frac{1}{3}^0=1$
$g(1)=\frac{1}{3}^1=\frac{1}{3}$
$g(2)=\frac{1}{3}^2=\frac{1}{9}$
For every corresponding x-value the following equation is true: $g(x)-2=f(x)$
This means that the graph is translated 2 units down.
Every $g(x)$ value will be decreased by 2.
(Because the original $f(x)$ will be equal to $(x)-2$ with the same x-value. For example if $f(0)=1$ in the original $f(x)$, this will be translated as $g(0)-2=1-2=-1$. We can see that here, the $g(x)$ is greater than $f(x)$ for every corresponding x-value by 2.)